TAWAASUL DAN WASILAH - Murjani Murjani (CV. Adiba Aisha Amira, 2022)
Tawassul with our good deeds and good deeds is allowed according to the agreement of the scholars'. Likewise tawassul to the Prophet s.a.w. also allowed according to the arguments above. There is no doubt that the prophet Muhammad SAW has a noble position with Allah SWT, so there is nothing wrong if we rely on Allah's most beloved lover, and so do pious people.